Solar Cells
By introducing compound semiconductor layers containing Na, Zn and O in perovskite solar cells, the interface loss problem caused by heterogeneous interfaces is solved, and high conversion efficiency and open circuit voltage are improved.
Patent Information
- Application Number
- CN201980093442.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-11
- Filing Date
- 2019-10-07
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2039-10-07
AI Technical Summary
Existing perovskite solar cells have challenges in improving voltage values and conversion efficiency, especially because interface losses due to heterogeneous interfaces are difficult to reduce.
By placing a semiconductor layer containing compounds containing Na, Zn and O between the photoelectric conversion layer and the electrode, the deep defect energy level at the interface is reduced, thereby suppressing interface loss.
It has achieved high conversion efficiency and improvement of open circuit voltage of perovskite solar cells, and is suitable for perovskite solar cells, CIS-based solar cells and organic-based solar cells.
Smart Images

Figure CN113508473B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to solar cells. Background Art
[0002] In recent years, perovskite solar cells have been studied and developed. In perovskite solar cells, a perovskite compound represented by the chemical formula ABX3 is used as a light absorbing material, wherein A is a monovalent cation, B is a divalent cation, and X is a halogen anion.
[0003] In non-patent document 1, a perovskite compound represented by the chemical formula CH3NH3PbI3 is disclosed as a light absorbing material for a perovskite solar cell. In addition, in non-patent document 1, TiO2 and Spiro-OMeTAD are disclosed as electron transport materials and hole transport materials, respectively.
[0004] Prior art literature
[0005] Non-patent literature
[0006] Non-patent document 1: "Sequential deposition as a route to high-performance perovskite-sensitized solar cells", Nature, vol. 499, pp. 316-319, 18 July 2013 [DOI: 10.1038 / nature12340]
[0007] Non-patent document 2: "Research Direction toward Theoretical Efficiency in Perovskite Solar Cells", ACS Photonics, 2018, 5(8), pp 2970-2977 [DOI: 10.1021 / acsphotonics.8b00124]
[0008] Non-patent document 3: "Room-Temperature Formation of Highly CrystallineMultication Perovskites for Efficient, Low-Cost Solar Cells", Advanced Materials, Volume 29, Issue 15, April 18, 2017, 1606258 [DOI: 10.1002 / adma.201606258] Summary of the invention
[0009] Problems to be solved by the invention
[0010] The purpose of this application is to provide a technology for improving the conversion efficiency of solar cells.
[0011] Means for solving problems
[0012] The solar cell of the present application has:
[0013] 1st electrode;
[0014] The second electrode;
[0015] a photoelectric conversion layer located between the first electrode and the second electrode; and
[0016] a semiconductor layer located between the first electrode and the photoelectric conversion layer,
[0017] wherein at least one electrode selected from the first electrode and the second electrode has light-transmitting properties,
[0018] The semiconductor layer includes a compound containing Na, Zn, and O.
[0019] Effects of the Invention
[0020] The present application provides a solar cell with high conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A cross-sectional view showing a solar cell according to an embodiment of the present application.
[0022] Figure 2 The X-ray diffraction (hereinafter referred to as "XRD") spectrum of each semiconductor layer produced in the example shows the vicinity of the peak corresponding to the (202) plane of Na2Zn2O3.
[0023] Figure 3 The XRD spectrum of each semiconductor layer produced in the example shows the vicinity of the peak corresponding to the (202) plane of Na2Zn2O3. DETAILED DESCRIPTION
[0024] <Definition of terms>
[0025] The term "perovskite compound" used in this specification refers to a perovskite crystal structure represented by the chemical formula ABX3 (wherein A is a monovalent cation, B is a divalent cation, and X is a halogen anion) and a structure having a crystal similar thereto. The term "perovskite solar cell" used in this specification refers to a solar cell containing a perovskite compound as a light absorbing material.
[0026] <Insights that form the basis of this application>
[0027] The findings that form the basis of the present application are as follows.
[0028] In perovskite solar cells, the conversion efficiency has also been greatly improved in recent years. The conversion efficiency of a solar cell is expressed by the product of the voltage value and the current value. Regarding perovskite solar cells, current values close to the theoretical limit value have been reported. However, there is still a deviation between the reported voltage value and the theoretical limit value. The increase in voltage value is an important factor in improving the conversion efficiency (see non-patent document 2).
[0029] Generally speaking, in solar cells, the loss of voltage value is considered to be caused by interface loss. In order to increase the voltage value, the reduction of interface loss will be considered. The inventors of the present invention have found that by configuring a semiconductor layer containing compounds containing Na, Zn and O between the photoelectric conversion layer and the electrode, it is not easy to form deep defect energy levels that can become a loss factor at the interface, and the interface loss is suppressed. It should be noted that for previous crystalline solar cells having an interface composed of homogeneous materials (i.e., homogeneous interfaces), such as gallium arsenic solar cells and silicon solar cells, the interface loss can be reduced relatively easily by reducing the density of defects at the interface. On the other hand, perovskite solar cells have an interface composed of different materials (i.e., heterogeneous interfaces). Therefore, for perovskite solar cells, it is difficult to reduce the density of defects at the interface. However, according to the technology of the present application obtained based on the above insights, it is possible to achieve an increase in the voltage value and conversion efficiency in perovskite solar cells. In addition, the technology can also be applied to CIS solar cells and organic solar cells. In addition, the increase in voltage value can be confirmed by the increase in open circuit voltage.
[0030] <Implementation Methods of the Application>
[0031] Hereinafter, embodiments of the present application will be described with reference to the accompanying drawings.
[0032] Figure 1 is a cross-sectional view of a solar cell according to this embodiment. Figure 1 As shown in , the solar cell 100 of the present embodiment includes: a first electrode 2, a second electrode 6, a photoelectric conversion layer 4, and a semiconductor layer 3. The photoelectric conversion layer 4 is located between the first electrode 2 and the second electrode 6. The semiconductor layer 3 is located between the first electrode 2 and the photoelectric conversion layer 4. The first electrode 2 is opposite to the second electrode 6 in such a manner that the semiconductor layer 3 and the light absorption layer 4 are arranged between the first electrode 2 and the second electrode 6. At least one electrode selected from the first electrode 2 and the second electrode 6 has light transparency. In this specification, the so-called "electrode has light transparency" means that 10% or more of light at any wavelength in light having a wavelength of 200nm to 2000nm passes through the electrode.
[0033] The semiconductor layer 3 includes a compound A containing Na, Zn and O. Compound A is usually a semiconductor. Compound A may also be a crystal. Compound A may also be Na2Zn2O3. In other words, the semiconductor layer 3 may also include Na2Zn2O3. However, the composition of compound A is not limited to Na2Zn2O3. The semiconductor layer 3 may also include two or more compounds A having different compositions. Whether the semiconductor layer 3 includes crystals of Na2Zn2O3 can be confirmed by XRD.
[0034] The composition ratio (Na / Zn) of Na to Zn in compound A may also be 0.769 or more. The above composition ratio is an atomic ratio. When the composition ratio (Na / Zn) is 0.769 or more, Na2Zn2O3 is easily formed. The composition ratio (Na / Zn) of Na to Zn in compound A may also be 2.333 or less. When the composition ratio (Na / Zn) is 2.333 or less, the formation of compound A having a composition other than Na2Zn2O3 may be suppressed. The composition ratio (Na / Zn) may also be 0.769 to 2.333.
[0035] The semiconductor layer 3 may be formed of a plurality of layers having the same composition or a plurality of layers having different compositions. When the semiconductor layer 3 is formed of a plurality of layers, the layer on the photoelectric conversion layer 4 side may contain compound A.
[0036] The semiconductor layer 3 may also be an electron transport layer.
[0037] The semiconductor layer 3 may also contain a substance other than the compound A. The substance is usually a semiconductor. The substance that the semiconductor layer 3 may contain is, for example, a semiconductor S1 having an energy gap of 3.0 eV or more. When the semiconductor layer 3 contains the semiconductor S1 and the compound A, the transmission of visible light and infrared light through the semiconductor layer 3 to the photoelectric conversion layer 4 becomes more reliable. Examples of the semiconductor S1 are organic n-type semiconductors and inorganic n-type semiconductors.
[0038] Examples of organic n-type semiconductors are imide compounds, quinone compounds, fullerenes and their derivatives. Examples of inorganic n-type semiconductors are oxides of metal elements and perovskite oxides. Examples of metal elements are Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga and Cr. A specific example of a metal oxide is TiO2. Examples of perovskite oxides are SrTiO3 and CaTiO3.
[0039] The semiconductor layer 3 may also contain a substance having an energy gap greater than 6.0 eV. Examples of substances having an energy gap greater than 6.0 eV include: (i) alkali metal halides such as lithium fluoride; (ii) alkaline earth metal halides such as calcium fluoride; (iii) base metal oxides such as magnesium oxide; and (iv) silicon dioxide. When the semiconductor layer 3 contains such a substance and is an electron transport layer, the thickness of the semiconductor layer 3 is, for example, 10 nm or less in order to ensure electron transport properties.
[0040] The semiconductor layer 3 may be in contact with the photoelectric conversion layer 4. The semiconductor layer 3 may be in contact with the first electrode 2.
[0041] exist Figure 1 In the solar cell 100 shown in , a first electrode 2, a semiconductor layer 3, a photoelectric conversion layer 4, a hole transport layer 5, and a second electrode 6 are sequentially stacked on a substrate 1. In the solar cell of the present application, a second electrode 6, a hole transport layer 5, a photoelectric conversion layer 4, a semiconductor layer 3, and a first electrode 2 may also be sequentially stacked on a substrate 1. The solar cell of the present application may not include a substrate 1. The solar cell of the present application may not include a hole transport layer 5.
[0042] The basic effects of the solar cell 100 are described. When the solar cell 100 is irradiated with light, the photoelectric conversion layer 4 absorbs the light and generates excited electrons and holes. The excited electrons move to the semiconductor layer 3. The holes move to the hole transport layer 5. The semiconductor layer 3 and the hole transport layer 5 are electrically connected to the first electrode 2 and the second electrode 6, respectively. Current is extracted from the first electrode 2 and the second electrode 6, which function as a negative electrode and a positive electrode, respectively.
[0043] Hereinafter, each component of the solar cell 100 will be described in detail.
[0044] (Substrate 1)
[0045] The substrate 1 supports each layer constituting the solar cell 100. The substrate 1 can be formed of a transparent material. Examples of the substrate 1 are a glass substrate and a plastic substrate. The plastic substrate can also be a plastic film. In the case where the first electrode 2 has sufficient strength to support each layer, the solar cell 100 may not include the substrate 1.
[0046] (First electrode 2 and second electrode 6)
[0047] The first electrode 2 and the second electrode 6 are conductive. At least one electrode selected from the first electrode 2 and the second electrode 6 is light-transmitting. For example, light in the visible to near-infrared region passes through the light-transmitting electrode. The light-transmitting electrode can be composed of, for example, a transparent and conductive metal oxide. Examples of transparent and conductive metal oxides are: (i) indium-tin composite oxide; (ii) tin oxide doped with antimony; (iii) tin oxide doped with fluorine; (iv) zinc oxide doped with at least one element selected from boron, aluminum, gallium and indium; and (v) composites thereof.
[0048] The light-transmitting electrode may also be an electrode made of an opaque material and having a pattern shape through which light can pass. Examples of light-transmitting pattern shapes are linear (striped), wavy line, lattice (mesh), and punched metal shapes in which a plurality of fine through holes are regularly or irregularly arranged. In the case of electrodes having the above-mentioned pattern shapes, light can pass through the openings in the electrode where no electrode material is present. Examples of opaque materials are platinum, gold, silver, copper, aluminum, rhodium, indium, titanium, iron, nickel, tin, zinc, and alloys containing any of them. The material may also be a conductive carbon material.
[0049] Solar cell 100 includes semiconductor layer 3 between first electrode 2 and photoelectric conversion layer 4. Therefore, first electrode 2 may not have the property of blocking holes moving from photoelectric conversion layer 4. First electrode 2 may be made of a material capable of forming ohmic contact with photoelectric conversion layer 4.
[0050] In the case where the solar cell 100 does not have the hole transport layer 5, the second electrode 6 has a property of blocking electrons moving from the photoelectric conversion layer 4 (hereinafter referred to as "electron blocking property"). In this case, the second electrode 6 is not in ohmic contact with the photoelectric conversion layer 4. In this specification, the so-called electron blocking property refers to a property of allowing only holes generated in the photoelectric conversion layer 4 to pass through and not allowing electrons to pass through. The Fermi level of the material having the electron blocking property is lower than the energy level at the lower end of the conduction band of the photoelectric conversion layer 4.
[0051] The Fermi level of the material having an electron blocking property may be lower than the Fermi level of the photoelectric conversion layer 4 .
[0052] Examples of materials with electron blocking properties are carbon materials such as platinum, gold, and graphene. In addition, these materials do not have light transmittance. Therefore, when using these materials to form a light-transmitting electrode, for example, an electrode having a pattern shape such as the above is adopted.
[0053] When the solar cell 100 includes the hole transport layer 5 between the second electrode 6 and the photoelectric conversion layer 4 , the second electrode 6 may not have electron blocking properties. In this case, the second electrode 6 may be made of a material capable of forming an ohmic contact with the photoelectric conversion layer 4 .
[0054] The light transmittance of the first electrode 2 and the second electrode 6 may be 50% or more, or 80% or more. The wavelength of light transmitted through the electrodes depends on the absorption wavelength of the photoelectric conversion layer 4. The thickness of each of the first electrode 2 and the second electrode 6 is, for example, 1 nm to 1000 nm.
[0055] (Photoelectric conversion layer 4)
[0056] The photoelectric conversion layer 4 may also include a perovskite compound composed of a monovalent cation, a divalent cation and a halogen anion as a light absorbing material. In this case, the solar cell 100 is a perovskite solar cell. As described above, the perovskite compound is a perovskite crystal structure represented by the chemical formula ABX3 and a structure having a crystal similar thereto. A is a monovalent cation, B is a divalent cation and X is a halogen anion. Examples of the monovalent cation A are alkali metal cations and organic cations. A specific example of the cation A is a methylammonium cation (CH3NH3 + ), formamidinium cation (NH2CHNH2 + ) and cesium cation (Cs + ). Examples of the divalent cation B are Pb cation (lead cation) and Sn cation. The divalent cation B may also be a Pb cation. The sites of the cation A, cation B and anion X may be occupied by multiple types of ions.
[0057] The photoelectric conversion layer 4 may also mainly contain a perovskite compound. The photoelectric conversion layer 4 may also be substantially made of a perovskite compound. In this specification, the so-called "mainly containing" a certain substance means that the content of the substance is 50% by mass or more, and the content of the substance may also be 60% by mass or more, 70% by mass or more, and further 80% by mass or more. In this specification, the so-called "substantially made of" a certain substance means that the content of the substance is 90% by mass or more, and the content of the substance may also be 95% by mass or more. The photoelectric conversion layer 4 may further contain compounds other than the perovskite compound. The photoelectric conversion layer 4 may contain impurities.
[0058] The photoelectric conversion layer 4 is not limited to the above examples. The photoelectric conversion layer 4 may also mainly include a compound semiconductor constituting a photoelectric conversion layer of a CIS solar cell, or may be substantially made of the compound semiconductor. A typical example of a compound semiconductor mainly includes copper (Cu), indium (In) and selenium (Se).
[0059] The technology of the present application is particularly advantageous for perovskite solar cells whose conversion efficiency is difficult to improve due to the presence of heterojunction interfaces.
[0060] The thickness of the photoelectric conversion layer 4 is, for example, 100 nm to 10 μm. The thickness of the photoelectric conversion layer 4 may also be 100 nm to 1000 nm. The thickness of the photoelectric conversion layer 4 may depend on the magnitude of light absorption of the photoelectric conversion layer 4 .
[0061] (Hole Transport Layer 5)
[0062] Figure 1 The solar cell 100 shown in FIG. 1 further includes a hole transport layer 5 located before the second electrode 6 and the photoelectric conversion layer 4. The hole transport layer 5 is composed of, for example, an organic semiconductor or an inorganic semiconductor. The hole transport layer 5 may include a plurality of layers composed of different materials.
[0063] Examples of organic semiconductors are phenylamine and triphenylamine derivatives containing tertiary amines in the skeleton and PEDOT compounds containing a thiophene structure. The molecular weight of the organic semiconductor is not limited. The organic semiconductor can also be a polymer. Representative examples of organic semiconductors are: (i) spiro-OMeTAD: 2,2',7,7'-tetrakis-(N,N-di-p-methoxyphenylamine)-9,9'-spirobifluorene; (ii) PTAA: poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] ,4,6-trimethylphenyl)amine]); (iii) P3HT: poly(3-hexylthiophene-2,5-diyl); (iv) PEDOT: poly(3,4-ethylenedioxythiophene); and (v) CuPC: copper(II)phthalocyanine triple-sublimed grade.
[0064] Examples of inorganic semiconductors are Cu2O, CuGaO2, CuSCN, CuI, NiO x 、MoO x , V2O5 and carbon-based materials such as graphene oxide.
[0065] The thickness of the hole transport layer 5 may be 1 nm to 1000 nm, or 10 nm to 500 nm. The hole transport layer 5 having a thickness within this range can have a high hole transport property.
[0066] The hole transport layer 5 may contain a supporting electrolyte and a solvent. The supporting electrolyte and the solvent can stabilize the holes in the hole transport layer 5.
[0067] Examples of supporting electrolytes are ammonium salts and alkali metal salts. Examples of ammonium salts are tetrabutylammonium perchlorate, tetraethylammonium hexafluorophosphate, imidazolium salts, and pyridinium salts. Examples of alkali metal salts are LiN(SO2C n F 2n+1 )2. LiPF6, LiBF4, lithium perchlorate and potassium boron tetrafluoride.
[0068] The solvent that may be included in the hole transport layer 5 may also have high ion conductivity. The solvent may be any of an aqueous solvent and an organic solvent. From the viewpoint of stabilization of the solute, the solvent may also be an organic solvent. Examples of organic solvents are heterocyclic compounds such as tert-butylpyridine, pyridine, and n-methylpyrrolidone.
[0069] The solvent that may be contained in the hole transport layer 5 may also be an ionic liquid. The ionic liquid may be used alone or in a mixture with other solvents. The advantages of the ionic liquid are low volatility and high flame retardancy.
[0070] Examples of the ionic liquid include imidazolium compounds such as 1-ethyl-3-methylimidazolium tetracyanoborate, pyridine compounds, alicyclic amine compounds, aliphatic amine compounds, and azoinium amine compounds.
[0071] (Other layers)
[0072] The solar cell 100 may have other layers other than those described above. An example of other layers is a porous layer. The porous layer is, for example, located between the semiconductor layer 3 and the photoelectric conversion layer 4. The porous layer includes a porous body. The porous body includes pores. The pores contained in the porous layer located between the semiconductor layer 3 and the photoelectric conversion layer 4 are connected from the portion in contact with the semiconductor layer 3 to the portion in contact with the photoelectric conversion layer 4. The pores are typically filled with a material constituting the photoelectric conversion layer 4, and electrons can move directly from the photoelectric conversion layer 4 to the semiconductor layer 3.
[0073] The porous layer can serve as a base when the photoelectric conversion layer 4 is formed on the first electrode 2 and the semiconductor layer 3. The porous layer does not hinder light absorption by the photoelectric conversion layer 4 and movement of electrons from the photoelectric conversion layer 4 to the semiconductor layer 3.
[0074] The porous body that can constitute the above-mentioned porous layer is composed of, for example, a connection of particles of an insulator or a semiconductor. Examples of insulating particles are aluminum oxide particles and silicon oxide particles. Examples of semiconductor particles are inorganic semiconductor particles. Examples of inorganic semiconductors are oxides of metal elements, perovskite oxides of metal elements, sulfides of metal elements, and metal chalcogenides. Examples of oxides of metal elements are oxides of each metal element of Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, Si, and Cr. A specific example of an oxide of a metal element is TiO2. Examples of perovskite oxides of metal elements are SrTiO3 and CaTiO3. Examples of sulfides of metal elements are CdS, ZnS, In2S3, PbS, Mo2S, WS2, Sb2S3, Bi2S3, ZnCdS2, and Cu2S. Examples of metal chalcogenides are CdSe, In2Se3, WSe2, HgS, PbSe and CdTe.
[0075] The thickness of the porous layer may be 0.01 μm to 10 μm, or 0.1 μm to 1 μm. The porous layer may have a large surface roughness. Specifically, the surface roughness coefficient of the porous layer given as the value of effective area / projected area may be greater than 10, or greater than 100. In addition, the so-called projected area refers to the area of the shadow formed on the back of the object when the object is irradiated with light from the opposite side. The effective area refers to the actual surface area of the object. The effective area can be calculated by (i) the volume calculated from the projected area and thickness of the object, (ii) the specific surface area of the material constituting the object, and (iii) the volume density of the material constituting the object.
[0076] The solar cell 100 is produced, for example, by the following method.
[0077] First, the first electrode 2 is formed on the surface of the substrate 1. The first electrode 2 can be formed by a chemical vapor deposition (hereinafter referred to as "CVD") method or a sputtering method.
[0078] Next, a semiconductor layer 3 is formed on the first electrode 2. A coating method such as a spin coating method can be used to form the semiconductor layer 3. The semiconductor layer 3 contains a compound containing Na, Zn and O. In the case of forming the semiconductor layer 3 by a coating method, a solution obtained by dissolving a Na raw material and a Zn raw material in a solvent in a specified ratio is coated on the first electrode 2 by a coating method such as a spin coating method. The formed coating film can be fired in air at a specified temperature. The specified temperature is, for example, 300°C to 500°C. An example of a Na raw material is sodium acetate. An example of a Zn raw material is zinc acetate. An example of a solvent is ethoxymethanol, isopropyl alcohol or ethanol. By adjusting the amount of the Na raw material and the Zn raw material contained in the coating solution, the composition ratio (Na / Zn) in the above-mentioned compounds can be controlled.
[0079] Next, the photoelectric conversion layer 4 is formed on the semiconductor layer 3. The photoelectric conversion layer 4 containing the perovskite compound as the light absorbing material can be formed by a coating method such as a spin coating method.
[0080] Next, a hole transport layer 5 is formed on the photoelectric conversion layer 4. The hole transport layer 5 can be formed by coating or printing. Examples of coating methods are doctor blade method, rod coating method, spray method, dip coating method and spin coating method. An example of printing method is screen printing method. It is also possible to form a film by mixing a plurality of materials, and then pressurizing or firing to form the hole transport layer 5. The hole transport layer 5 composed of an organic low molecular weight substance or an inorganic semiconductor can also be formed by vacuum evaporation method.
[0081] Next, the second electrode 6 is formed on the hole transport layer 5. The second electrode 6 can be formed by a CVD method or a sputtering method.
[0082] In this manner, the solar cell 100 is obtained. However, the method for manufacturing the solar cell 100 is not limited to the above method.
[0083] (Example)
[0084] Hereinafter, the solar cell of the present application will be described in more detail with reference to the examples. However, the solar cell of the present application is not limited to the embodiments shown in the following examples.
[0085] (Example 1)
[0086] Referring to non-patent document 3, a Figure 1 The solar cell of Example 1 is a perovskite solar cell having the same structure as the solar cell 100 shown in FIG. The elements constituting the solar cell of Example 1 are as follows.
[0087] Substrate 1: Glass substrate
[0088] First electrode 2: Indium-doped SnO2 layer (manufactured by GEOMATEC, surface resistivity 10Ω / sq)
[0089] Semiconductor layer 3: layer containing compound Na2Zn2O3 (thickness 10nm)
[0090] Photoelectric conversion layer 4: a layer mainly containing CH(NH2)PbI3 which is a perovskite compound.
[0091] Hole transport layer 5: PTAA layer (containing LiN(SO2C2F5)2 and 4-tert-butylpyridine (t-BP) as supporting electrolyte and solvent, respectively)
[0092] Second electrode 6: Gold layer (thickness 80nm)
[0093] The specific production method is shown below.
[0094] First, as substrate 1 and first electrode 2, a 1 mm thick conductive glass substrate (manufactured by Nippon Sheet Glass Co., Ltd.) having an indium-doped SnO 2 layer formed on the surface was prepared in a dry room under a dry atmosphere having a dew point of -40°C or less.
[0095] Next, a mixed solution of sodium acetate (manufactured by Wako) and zinc acetate (manufactured by Aldrich) is applied on the first electrode 2 by spin coating. The mixed solution is a solution of ethoxymethanol (manufactured by Aldrich) in which sodium acetate and zinc acetate are dissolved in a molar ratio of 1:1. The concentrations of sodium acetate and zinc acetate in the mixed solution are 0.55 mol / L, respectively. Next, the first electrode 2 coated with the mixed solution is heat-treated using a hot plate to form a semiconductor layer 3 containing Na2Zn2O3. The heat treatment is performed at 130°C / 10 minutes, and then at 350°C / 10 minutes. The formed semiconductor layer 3 functions as an electron transport layer.
[0096] Next, the first raw material solution was applied on the semiconductor layer 3 by spin coating to form the photoelectric conversion layer 4. The first raw material solution was an N,N-dimethylformamide (manufactured by Acros) solution and contained the following compounds.
[0097] 0.92 mol / L PbI2 (manufactured by Tokyo Chemical Industry Co., Ltd.),
[0098] 0.17 mol / L PbBr2 (produced by Tokyo Chemical Industry),
[0099] 0.83 mol / L of formamidinium iodide (FAI: manufactured by Great Cell Solar),
[0100] 0.17 mol / L methylammonium bromide (MABr: manufactured by Great Cell Solar),
[0101] · Dimethyl sulfoxide (manufactured by Acros) containing 0.05 mol / L CsI (manufactured by Iwatani Sangyo)
[0102] The mixing ratio of dimethyl sulfoxide and N,N-dimethylformamide in the first raw material solution was 1:4 in terms of volume ratio.
[0103] Next, the second raw material solution was applied on the photoelectric conversion layer 4 by spin coating to form the hole transport layer 5. The second raw material solution was a toluene (made by Acros) solution and contained the following compounds.
[0104] 10 mg of PTAA (Aldrich),
[0105] 5 μL of tBP (Aldrich),
[0106] 4 μL of LiN(SO2C2F5)2 (Tokyo Chemical) acetonitrile solution (concentration 1.8 mol / L)
[0107] Finally, a gold layer with a thickness of 80 nm was deposited on the hole transport layer 5 by vapor deposition to form the second electrode 7 .
[0108] In this manner, a solar cell of Example 1 was obtained. In addition, the evaluations described in the items [Evaluation of semiconductor layer 3] and [Evaluation of solar cell characteristics] below were also performed in a dry room.
[0109] (Example 2~Example 10)
[0110] Solar cells of Examples 2 to 10 were produced in the same manner as in Example 1, except that the mixing ratio (molar ratio) of sodium acetate and zinc acetate in the mixed solution used for forming the semiconductor layer 3 was changed as shown in Table 1 below.
[0111] [Evaluation of Semiconductor Layer 3]
[0112] For each solar cell of Examples 1 to 10, XRD analysis was performed on the semiconductor layer 3. The XRD analysis was performed on the semiconductor layer 3 exposed by peeling off the second electrode 7 and dissolving and removing the hole transport layer 5 using a solvent. As the solvent, N,N-dimethylformamide was used. For the XRD analysis, an X-ray diffraction measuring device (Rigaku, Cu anode, λ=0.15418 nm) was used. The XRD analysis was performed based on the 2θ / θ method performed on the thin film.
[0113] The results of the XRD analysis are shown in Table 1 below together with the mixing ratio of sodium acetate and zinc acetate in the mixed solution used for forming the semiconductor layer 3 and the composition ratio Na / Zn calculated from the mixing ratio. In addition, the XRD curves of the semiconductor layer 3 having a mixing ratio in the range of 9:1 to 4:6 and the semiconductor layer 3 having a mixing ratio in the range of 1:1.1 to 1:1.4 are shown in Table 1. Figure 2 and Figure 3 It should be noted that Figure 2 and Figure 3 ] The vicinity of the peak (2θ / θ = 34.8°) corresponding to the (202) plane of Na2Zn2O in the XRD curve is shown.
[0114] As shown in Table 1, Figure 2 and Figure 3 As shown in , when the composition ratio Na / Zn is less than 0.714, the peak corresponding to the (202) plane of Na2Zn2O3 is not observed. On the other hand, when the composition ratio Na / Zn is greater than 0.769, the peak is observed. This means that: when the composition ratio Na / Zn is less than 0.714, Na2Zn2O3 is not included in the semiconductor layer 3, but when the composition ratio Na / Zn is greater than 0.769, Na2Zn2O3 is included in the semiconductor layer 3. In addition, when the composition ratio Na / Zn is greater than 4.000, in addition to the above-mentioned peak derived from Na2Zn2O3, a peak of an impurity phase is observed at a diffraction angle 2θ / θ of greater than 35°. On the other hand, when the composition ratio Na / Zn is less than 2.333, the peak of the impurity phase is not observed, and the above-mentioned peak of approximately pure Na2Zn2O3 is observed. This means that when the composition ratio Na / Zn is 2.333 or less, a Na2Zn2O3 layer with less impurities can be formed.
[0115] [Table 1]
[0116]
[0117] (Example 11)
[0118] A solar cell of Example 11 as a comparative example was obtained in the same manner as Example 1 except that the solution applied on the first electrode 2 was changed from the mixed solution to an ethoxymethanol solution (concentration: 0.55 mol / L) in which only zinc acetate was dissolved. This solar cell had an electron transport layer composed of ZnO.
[0119] (Example 12)
[0120] A solar cell of Example 12 as a comparative example was obtained in the same manner as in Example 11, except that the substrate 1 and the first electrode 2 on which the electron transport layer composed of ZnO was formed were immersed in a NaOH aqueous solution (concentration of 0.01 mol / L) for 60 seconds to perform Na treatment on the surface of the electron transport layer before forming the photoelectric conversion layer 4. The solar cell includes an electron transport layer composed of ZnO and having a Na-treated surface.
[0121] (Example 13)
[0122] A solar cell of Example 13 as a comparative example was obtained in the same manner as Example 1 except that the solution applied on the first electrode 2 was changed from the above-mentioned mixed solution to a mixed solution of sodium carbonate (manufactured by Wako) and zinc acetate. The mixed solution used in Example 13 was a solution of ethoxymethanol in which sodium carbonate and zinc acetate were dissolved in a molar ratio of 1:1. The concentrations of sodium carbonate and zinc acetate in the mixed solution were 0.55 mol / L, respectively. The solar cell had an electron transport layer composed of a mixture of sodium carbonate (Na2CO3) and ZnO.
[0123] (Example 14)
[0124] A solar cell of Example 14 as a comparative example was obtained in the same manner as in Example 1, except that the semiconductor layer 3 was not formed and the electron transport layer composed of TiO 2 was formed by sputtering.
[0125] [Evaluation of Solar Cell Characteristics]
[0126] The open circuit voltage and conversion efficiency of each produced solar cell were evaluated using a solar simulator (ALS440B manufactured by BAS). The evaluation was performed at an illuminance of 100 mW / cm 2 It is implemented by simulating sunlight.
[0127] The solar cell characteristics of Examples 1 and 11 to 14 are shown in Table 2 below.
[0128] [Table 2]
[0129]
[0130] As shown in Table 2, the solar cell of Example 1 having a semiconductor layer 3 containing a compound containing Na, Zn, and O shows a higher open circuit voltage and conversion efficiency than the solar cells of Examples 11 to 14 not having the semiconductor layer 3. In addition, by comparing Example 1 with Examples 12 and 13, it is known that in order to obtain the high open circuit voltage and conversion efficiency, a semiconductor layer 3 in which Na, Zn, and O exist in the form of a compound is required.
[0131] Industrial Applicability
[0132] The solar cell of the present application can be used for various applications including applications of conventional solar cells.
[0133] Explanation of symbols
[0134] 1 substrate
[0135] 2 1st electrode
[0136] 3 Semiconductor layer
[0137] 4 Photoelectric conversion layer
[0138] 5 Hole transport layer
[0139] 6. Second electrode
[0140] 100 Solar Cells
Claims
1. A solar cell comprising: 1st electrode; The second electrode; a photoelectric conversion layer located between the first electrode and the second electrode; and a semiconductor layer located between the first electrode and the photoelectric conversion layer, in, At least one electrode selected from the first electrode and the second electrode has light-transmitting properties, and The semiconductor layer includes a compound containing Na, Zn and O, The composition ratio of Na to Zn in the compound (Na / Zn) is 0.769 or more, where the composition ratio is an atomic ratio. The solar cell is a perovskite solar cell, a CIS solar cell or an organic solar cell.
2. The solar cell according to claim 1, wherein: The composition ratio of Na to Zn (Na / Zn) in the compound is 2.333 or less.
3. The solar cell according to claim 1 or 2, wherein: The compound is Na2Zn2O3.
4. The solar cell according to claim 1 or 2, wherein: The semiconductor layer is in contact with the photoelectric conversion layer.
5. The solar cell according to claim 1 or 2, wherein: The semiconductor layer is an electron transport layer.
6. The solar cell according to claim 1 or 2, wherein: The solar cell further includes a hole transport layer located between the second electrode and the photoelectric conversion layer.
7. The solar cell according to claim 1 or 2, wherein: The photoelectric conversion layer includes a perovskite compound composed of monovalent cations, divalent cations, and halogen anions.
8. The solar cell according to claim 7, wherein: The divalent cation is a lead cation.